Cross-culture Negotiation of Indonesian Students - Anum, Adelina; Apriyanto, Sigit; Triana, Yunika (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
Indonesian students studying both at home and abroad, especially those taking the political negotiation course, are very much interested, but they do not understand the many cultural factors that must be taken into account when negotiating with other people from different backgrounds. This study aims to provide an overview of the understanding of Indonesian students of negotiation in intercultural settings. This study presents a literature review with primary data on articles, magazines, reports, and theories. This study indicates that a good cross-cultural understanding can increase the percentage of success in the research negotiation process. Cultural barriers such as the lack of foreign language skills in communication, a sense of ethnocentrism, and prejudice can hinder the study negotiation process.